A systematic review on internet addiction through various assessment tools among Chinese college student’s context - Yue, Li; Bakar, Zainudin Bin Abu; Ashari, Zakiah Binti Mohamad (Intelektual Pustaka Media Utama, 2024)
With the rapid development of information technology, the internet has evolved into an essential tool in everyday life. The global proportion of internet users has consistently risen in recent years. Notably, China boasts substantial internet users, with students representing the largest demographic, especially college students. The purpose of this study is to explore the issue of internet addiction among Chinese college students through various assessment tools. This study conducted a systematic literature review with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. A total of 409 publications were screened, and 23 were deemed eligible for inclusion in the review. The result revealed that there is no gold standard for evaluating internet addiction. Five types of instruments have been identified, and reported prevalence rates vary due to distinct assessment instruments and thresholds, spanning from 6.81% to 54.86%. Furthermore, internet addiction is associated with four factors among Chinese college students. Therefore, this study furnishes epidemiological evidence to support the prevention of internet addiction and the enhancement of mental health among college students.